Analisa Propeller Yang Tidak Balance dan Pengaruhnya Pada Kinerja Mesin di PT. Gamatara Trans Ocean Shipyard Cirebon - Santhi Wilastari; M. Robiatu MV. (Politeknik Bumi Akpelni Semarang, 2025)
The propeller plays a crucial role in the maritime industry, particularly in ship propulsion systems. However, it often experiences low performance, commonly due to imbalance. So this research aims to determine the damage and handling of unbalanced propellers and their solutions. An early indication of this problem is unstable rotation, which is generally caused by component damage or imbalance. This research highlights the damage found in the propeller and its shaft. The findings reveal significant erosion, wear, and cracking, particularly on the inner part of the shaft and the propeller blades. These damages result in imbalance, which negatively impacts other components and the overall propulsion performance. To address this issue, technical inspection and clarification by the Indonesian Classification Bureau (BKI) are necessary to ensure safety and restore the optimal function of the ship’s propulsion system.